FRAX—Where are we now?. Issue 3 (November 2015) - Compston, Juliet
Abstract: Bone mineral density (BMD) measurements have been widely used in clinical practice for the diagnosis of osteoporosis, monitoring of treatment, and prediction of fracture risk. However, although BMD values show high specificity for prediction of fractures, their sensitivity is quite low. Fracture risk algorithms such as FRAX improve prediction by including clinical risk factors that act independently of BMD. This mini-review discusses the strengths and limitations of FRAX relevant to its use in clinical practice.